Preferência por mapas em diferentes escalas para sistema de navegação e guia de rota em automóvel - Ramos, Ana Paula Marques; Decanini, Mônica Modesta Santos [UNESP]; Pugliesi, Edmur Azevedo [UNESP]; Tachibana, Vilma Mayumi [UNESP]; De Oliveira, Renan Furlan [UNESP]; Soares, Jader Mozella Marton [UNESP] (FapUNIFESP (SciELO), 2016)
Usability issues of maps presented in-car Route Guidance and Navigation System (RGNS) may result in serious impacts on traffic safety. To obtain effective RGNS, evaluation of ‘user satisfaction’ with the system has played a prominent role, since designers can quantify drivers’ acceptance about presented information. An important variable related to design of RGNS interfaces refers to select appropriate scale for maps, since it interferes on legibility of maps. Map with good legibility may support drivers comprehend information easily and take decisions during driving task quickly. This paper evaluates drivers’ preference for scales used in maps of RGNS. A total of 52 subjects participated of an experiment performed in a parked car. Maps were designed at four different scales 1:1,000, 1:3,000, 1:6,000 and 1:10,000 for a route composed of 13 junctions. Map design was based on cartographic communication principles, such as perceptive grouping and figure-ground segregation. Based on studies cases, we conclude intermediate scales (1:6,000 and 1:3,000) were more acceptable among drivers compared to large scales (1:1,000) and small (1:10,000). RGNS should select scales for maps which supports drivers to quickly identify direction of the maneuver and, simultaneously, get information about surroundings of route. More results are presented and implications discussed.
Preference for map scale of in-car route guidance and navigation system
Keywords: Drivers’ preference; In-car navigation; Maps at different scales; Usability